Sex in development : science, sexuality, and morality in global perspective - Adams, Vincanne, 1959-; Pigg, Stacy Leigh, 1960- (e-Duke books scholarly collection., 2005)
Ethnographic studies of the role of sexuality and gender in development discourse and policy.